Building the Quality of the Nation by Fostering a Literacy Culture for Elementary School Students during the Covid-19 Pandemic: Membangun Kualitas Bangsa dengan Menumbuhkan Budaya Literasi Siswa Sekolah Dasar di Masa Pandemi Covid-19 - Annam, Mohammad Choirul; Bandono, Adi (Universitas Muhammadiyah Sidoarjo, 2022)
Based on the recently released PISA (Program for International Student Assessment) report, Tuesday, December 3, 2019, Indonesia's reading score was ranked 72 out of 77 countries, mathematics scores were ranked 72 out of 78 countries, and science scores were ranked 70 out of 78 countries. . Data from international research institutions such as the Progress in International Reading Literacy Study (PIRLS), and Trends in International Mathematics and Science Studies (TIMS) show similar findings. In connection with this condition, the author wants to discuss the causal factors and how to improve the literacy culture of students in elementary schools. The approach method in this paper uses literacy studies. From various literatures it is found that there are three factors that cause low interest in reading. First, the lack of reading habits that are instilled from an early age. Second, the lack of book production in Indonesia as a result of the undeveloped regional publishers. Third, the lack of main educational facilities for internet-based information systems, which during the Covid'19 pandemic became the only reliable access to obtain various information, while not everyone has the ability to access the internet. Therefore, efforts are needed to solve the problem of low literacy culture. Various literatures suggest several efforts to improve literacy culture among elementary school students, including: firstly implementing the School Literacy Movement program launched by the Government, secondly holding literacy competitions such as writing competitions, reading poetry, etc., as well as reading corners in each class. , and the third held a one day one page program through assignments to read 1 page every day and summarize the reading results. Through these programs, it is expected to be able to improve the literacy culture of elementary school students and can systemically improve the quality of the nation.